A consensus-based set of measures for oral health care - Baâdoudi, F.; Trescher, Anna-Lena; Gabel, Frank; Listl, Stefan (Journal of dental research, 2017)
Increasingly more responsive and accountable health care systems are demanded, which is characterized by transparency and explicit demonstration of competence by health care providers and the systems in which they work. This study aimed to establish measures of oral health for transparent and explicit reporting of routine data to facilitate more patient-centered and prevention-oriented oral health care. To accomplish this, an intermediate objective was to develop a comprehensive list of topics that a range of stakeholders would perceive as valid, important, and relevant for describing oral health and oral health care. A 4-stage approach was used to develop the list of topics: 1) scoping of literature and its appraisal, 2) a meeting of experts, 3) a 2-stage Delphi process (online), and 4) a World Café discussion. The aim was to create consensus through structured conversations via a range of stakeholders (general dental practitioners, patients, insurers, and policy makers) from the Netherlands, Germany, the United Kingdom, Ireland, Hungary, and Denmark. The study was part of the ADVOCATE project, and it resulted in a list of 48 topics grouped into 6 clusters: 1) access to dental care, 2) symptoms and diagnosis, 3) health behaviors, 4) oral treatments, 5) oral prevention, and 6) patient perception. All topics can be measured, as they all have a data source with defined numerators and denominators. This study is the first to establish a comprehensive and multiple-stakeholder consented topic list designed for guiding the implementation of transparent and explicit measurement of routine data of oral health and oral health care. Successful measurement within oral health care systems is essential to facilitate learning from variation in practice and outcomes within and among systems, and it potentiates improvement toward more patient-centered and prevention-oriented oral health care.
Article first published online: April 7, 2017, Issue published: July 1, 2017
Gesehen am 30.05.2018